Synthesis and characterization of Poly(p-phenylenediamine) and its derivatives using aluminium triflate as a co-catalyst. Issue 1 (1st January 2018) - Amer, Ismael; Brandt, Sonja
Abstract: A series of p -phenylenediamine ( p PD), 2, 5−dimethyl- p -phenylenediamine (dMe- p PD) and 2, 3, 5, 6−tetramethyl- p -phenylenediamine (tMe- p PD) polymers were successfully synthesized in different polymerization conditions, using ammonium persulfate as an oxidant and aluminium triflate (Al(OTf)3 ) as a co-catalyst. The poly( p -phenylenediamine) (P( p PD)), poly(2, 5−dimethyl- p -phenylenediamine) (P(dMe- p PD)) and poly(2, 3, 5, 6−tetramethyl- p -phenylenediamine) (P(tMe- p PD)) polymers obtained were characterized by UV–vis, FT-IR, 1 H and 13 C NMR, WAXD, DSC and TGA. The addition of Al(OTf)3 to the polymerization reaction improved the polymerization yield of some polymers. In most solvents, significantly improved solubility of P(dMe- p PD) and P(Me- p PD) polymers was obtained compared to the P( p PD) polymers as a result of methyl side groups effects. The yield, structure and solubility of the polymers were shown to depend to a large extent on the polymerization conditions. The polymers displayed crystallization and melting transitions on DSC. The P( p PD), P(dMe- p PD) and P(tMe- p PD) polymers were found to have good thermal stability, as indicated by TGA results, and to decompose above 400°C in nitrogen.